TAK-242 affects Wallerian degeneration and peripheral nerve regeneration by regulating innate immunity in rats - Xiong, Le; Liang, Jie (International journal of clinical and experimental medicine, 2018)
Objective: The aim of this study is to distinguish whether Toll-like receptor 4 (TLR4) signaling is included in Wallerian degeneration (WD) and nerve regeneration or not after peripheral nerve injury. Methods: The rats were assigned into four groups randomly: sham group (n = 10), control group (n = 10), model group (n = 20), and treatment group (n = 20). The rats were treated with TAK-242 (0.15 mg/kg) or saline. TAK-242, a small molecular that inhibit TLR4 signaling was first given to rats intravenously 1 h before nerve injury and followed by daily injections for 7 consecutive days. Animals were sacrificed 1.5 h, 24 h, 3 d, 4 d, or 7 d after surgery. Real-time quantitative PCR (qRT-PCR) was adopted to test dynamic mRNA expressions of TIR-domain-containing adaptor inducing interferon-β (TRIF), interleukin-1 (IL-1β) and monocyte chemoattractant protein-1 (MCP-1). Immunofluorescence (IF) was used to test the expression of CD68+ macrophages and iba1+ Schwann cells in sciatic nerves. Luxol Fast Blue (LFB) staining was applied to test sciatic nerves myelin, and Haematoxylin-eosin (HE) staining was conducted in sciatic nerves tissue to observe the pathological variations. Immunohistochemistry (IHC) was applied to test the form of TRIF and growth associated protein-43 (GAP-43) in sciatic nerve, and sciatic function index (SFI) was applied to assess the recovery of motor function in rats. Results: The expressions of TRIF, IL-1β, MCP-1 and recruitments of Schwann cells and macrophages in sciatic nerve of rats were decreased significantly in treatment group compared with model group after peripheral nerve injury. Myelin clearance and axonal regeneration were delayed in treatment group compared with model group. HE staining also indicated a poor organization of repair site in treatment group in distal stump. Finally, the SFI scores of treatment group at each time point (20, 30, and 40 d post-injury) was lower than that of model group. Conclusions: TLR4 signaling might affect myelin phagocytosis and nerve regeneration during WD in rat after peripheral nerve injury via regulating the innate immune response.
Gesehen am 16.04.2020